1998
DOI: 10.1002/stem.160166
|View full text |Cite
|
Sign up to set email alerts
|

SCID Mouse Models of Human Stem Cell Engraftment

Abstract: The discovery of the severe combined immunodeficiency (scid) mouse mutation has provided a tool for establishment of small animal models as hosts for the in vivo analysis of normal and malignant human pluripotent hemopoietic stem cells. Intravenous injection of irradiated scid mice with human bone marrow, cord blood, or G-CSF cytokine-mobilized peripheral blood mononuclear cells, all rich in human hemopoietic stem cell activity, results in the engraftment of a human hemopoietic system in the murine recipient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
214
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(221 citation statements)
references
References 120 publications
(147 reference statements)
3
214
0
4
Order By: Relevance
“…Several types of immunodeficient mice have successfully received transplants of human cells (reviewed in Greiner et al 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of immunodeficient mice have successfully received transplants of human cells (reviewed in Greiner et al 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many groups have utilized these human-mouse (hu/mu) hematopoietic chimeras as model systems to assess HSC biology [1][2][3][4][5][6][7][8][9]. An additional application of these hu/mu chimera models is to investigate the in vivo biology of cell types of the individual human hematopoietic lineages [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, consequences of mutations in the Btk tyrosine kinase gene are more severe for humans than for mice (5,6). Observations of that kind provide impetus for animal models that would efficiently support formation of human B cells from hemopoietic stem cells and nonobese diabetic (NOD) 4 /SCID mice are extremely interesting in that context (7)(8)(9). Many laboratories have shown that B cells are formed in these animals from transplanted human stem cells (8, 10 -12), but it remains unclear how closely this engraftment reflects normal steady-state conditions.…”
mentioning
confidence: 99%